Konfigurasi Dalam Pembentukan Hukum Parpol Dan Pemilu Di Indonesia - Muhaimin, Muhammad (Jurnal Rechten : Riset Hukum dan Hak Asasi Manusia, 2024)
A democratic political configuration will direct legal products to be responsive. In theory, the configuration of party law is often related to a country's government system. Even though the 1945 Constitution clearly states that the Indonesian government has a presidential model, since the early era there has been a multi-party system and there is no desire to change it to a two-party system. When forming election regulations, you must be aware that it does not trigger multiple meanings so that they are easy to understand and you should focus on all stages of the electoral system to ensure the democracy of an election. Legislation is the task of political party representatives in parliament (DPR). Political ideology and political parties will have an impact on people's thinking about the world of politics and how to take political action, as a basis for movement, and will be echoed in society. Normative methods were used for this research, namely based on literature or scientific knowledge from books, journals and the results of previous thesis research. Library research and sociological aspects are used to answer questions, including relying on the opinions of relevant experts and further strengthening validation.